Case Report: Toxic megacolon secondary to chronic constipation and cocaine consumption - Dimas, Bertha; Hernández, Guillermo; Peralta, Ivonne; Godinez, Ansony; Gutierrez, Gabriela; Cruz, Fernando (Frontiers in Surgery, 2024)
Toxic megacolon (TM) is a severe condition characterized by acute colonic dilation, with specific radiological and clinical signs. The multifactorial etiology of TM is primarily associated with inflammatory bowel disease and infections. However, TM remains a challenging complication due to its potential for rapid progression to life-threatening conditions. This report describes a rare case of TM in a 25-year-old male with a history of recurrent constipation and chronic cocaine consumption. Examination and imaging indicated acute intestinal obstruction with dilated colon segments and fecal impaction, necessitating an urgent laparotomy. Surgery revealed pan-colonic dilatation and sigmoid perforations, leading to a total colectomy and ileostomy. Chronic constipation, often perceived as benign, can escalate into a critical situation, possibly exacerbated by cocaine-induced muscle weakness and hypoxia. Evidence suggests that cocaine negatively affects the intestinal mucosa, potentially leading to ischemia. Chronic factors, including the use of enemas, may have contributed to megacolon development and perforation.Overall, this report underscores the critical elements of diagnosis and the importance of patients' medical history, particularly those with unusual risk profiles. In addition, it highlights the need for further research to fully understand the implications of these cases.